Factors Affecting Mother in Breast Feeding in Sigumpar Village, Sigumpar District, Toba Regency - Jane Wilda Irmawati Sirait (International Journal of Public Health Excellence (IJPHE), 2023)
Exclusive breastfeeding can reduce the risk of death in infants because breast milk contains colostrum rich in antibodies for body resistance and killer germs in large quantities. In addition, breast milk also contains an absorbent substance in the form of its own enzyme, which will not interfere with enzymes in the intestine. The research design used in this research is descriptive research using a cross-sectional approach, which aims to determine the factors that influence mothers' breastfeeding in Sigumpar Village. The research design used in this research is descriptive research using a cross-sectional approach, which aims to determine the factors that influence mothers' breastfeeding in Sigumpar Village. The reason for choosing Sigumpar Village was the success of all mothers who have babies 0–24 months in providing breast milk, which was taken from the data of midwives from Sigumpar Village. The results of research and discussion of research on the factors that influence mothers' breastfeeding, namely: According to demographic data on mothers who provide ASI to children aged 0–24 months based on work, the majority of respondents (40 people, or 71.4%) do not work, and based on sources of information by health workers, as many as 44 people (78.6%) do not work. From the factor of the role of health workers in supporting breastfeeding in mothers who have babies 0–24 months in the supportive category, there are 49 people (87.5%). From the factor of knowledge of mothers about breastfeeding who have babies 0–24 months in the category of good knowledge, there are 56 people (100%).